EFEKTIVITAS FORUM PENATAAN RUANG DAERAH PADA PROSES REVISI RENCANA TATA RUANG WILAYAH KABUPATEN LAMANDAU PROVINSI KALIMANTAN TENGAH TAHUN 2023 - Wiwit Widi Nugroho; Bulkani, Bulkani; Suffianoor, Suffianoor (Nusantara Hasana Journal, 2025)
This study aims to assess the effectiveness of the Regional Spatial Planning Forum (FPRD) in supporting the revision process of the Regional Spatial Plan (RTRW) of Lamandau Regency in 2023. FPRD plays an important role as a collaborative forum for stakeholders to provide input, criticism, and suggestions that can improve regional spatial planning that is more inclusive and sustainable. Using a mixed approach, this research combines quantitative methods with descriptive surveys and qualitative methods through exploratory data analysis. Data was collected through questionnaires, interviews, and documentation related to the RTRW revision process. The results of the analysis show that FPRD has a high level of effectiveness in the aspects of cross-sectoral coordination, active community participation, and the quality of recommendations relevant to regional development. Reliability test results showed a Cronbach's Alpha value of 0.96, indicating excellent consistency in the questionnaire instrument. The findings also revealed that collaboration between local government, community, and private sector through FPRD is very effective in achieving decisions that are responsive to sustainable development needs. However, the research also identified several obstacles, such as the technical capacity of FPR members and inter-agency coordination mechanisms that need to be improved. Overall, this research confirms the strategic role of FPRD in strengthening a more transparent, inclusive and accountable RTRW revision process